2016
DOI: 10.3345/kjp.2016.59.10.414
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and intelligence outcome in 8- to 16-year-old born small for gestational age

Abstract: PurposeWe investigated behavioral problems, attention problems, and cognitive function in children and adolescents born small for gestational age (SGA).MethodsForty-six SGA children born at term and 46 appropriate for gestational age (AGA) children born at term were compared. Psychiatric symptoms were examined with reference to the Korean-Child Behavior Checklist, Korean-Youth Self Report, and Attention Deficit Hyperactivity Disorder Rating Scale (ADHD-RS). Cognitive function was estimated using the Wechsler I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…SGA has been recognized as a risk factor for psychomotor retardation, speech delay, cognitive impairment, behavior problems, and poor intelligence outcome in later life. [ 31 , 50 56 ] Poor growth velocity during hospitalization (EUGR) was also related to poor psychomotor outcome in early childhood. [ 25 , 34 , 43 , 57 , 58 ] Thus, early and aggressive nutritional support for adequate body weight gain during hospitalization in VLBW infants, which may mitigate the risks of neurodevelopmental disorders, appears to be the current consensus of opinion in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…SGA has been recognized as a risk factor for psychomotor retardation, speech delay, cognitive impairment, behavior problems, and poor intelligence outcome in later life. [ 31 , 50 56 ] Poor growth velocity during hospitalization (EUGR) was also related to poor psychomotor outcome in early childhood. [ 25 , 34 , 43 , 57 , 58 ] Thus, early and aggressive nutritional support for adequate body weight gain during hospitalization in VLBW infants, which may mitigate the risks of neurodevelopmental disorders, appears to be the current consensus of opinion in the literature.…”
Section: Discussionmentioning
confidence: 99%
“… Study Country Years of Birth LBW(n) Birth Weight (g) Gestational Age (week) Measurement Tool Age at evaluation IQ Scores Study Design NBW(n) mean (SD/range) Mean (SD)/range mean (SD) 1 Yi KH et al . 96 , 2016 Korea 2003-2009 L 46 2110(315) ≥37 WISC-III 12 100.52(15.24) case-control study N 46 3280(460) ≥37 109.52(12.54) 2 Serenius et al . 10 , 2016 Sweden 2004–2007 L 371 779(170) 25.4(1.07) WISC-IV 6.5 83.4(14.8) cohort study N 367 3617(482) 39.9(1.13) 100.3(11.7) 3 Breeman et al .…”
Section: Resultsmentioning
confidence: 99%
“…Controversy exists regarding the nature of neurocognitive morbidity, which develops in SGA neonates. For example, some studies have shown neurocognitive deficits and decreased functional outcomes in SGA children, in particular attention deficit hyperactive disorder (ADHD) [ 12 , 18 , 19 ], while other studies did not find significant associations with SGA [ 14 , 20 ]. Our long-term follow up did not find an association between SGA and ADHD, but this may be explained by the fact that our study was hospital-based, and in most cases ADHD diagnosis is made in an outpatient setting.…”
Section: Discussionmentioning
confidence: 99%